2021
DOI: 10.1108/ijilt-07-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Insight into online teaching behaviour of lecturers in Zimbabwean universities during the COVID-19 era and beyond: issues and challenges

Abstract: PurposeThis study aims to establish the online teaching behaviour of university lecturers as well as examine issues and challenges for online teaching in universities in Zimbabwe during the COVID-19 era and beyond.Design/methodology/approachThe study assumed a quantitative approach that employed a structured questionnaire for data collection. Structural equation modelling using AMOS version 22 and independent samples t-test were used for data analysis. Confirmatory factor analysis was used for data purificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…Lastly, (Rudhumbu et al, 2021) examined 'Online Teaching Behaviours in Zimbabwean Universities during the COVID 19 era.' The findings proved that the majority of universities lack suitable ICT infrastructure, leadership support and training opportunities are minimal.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, (Rudhumbu et al, 2021) examined 'Online Teaching Behaviours in Zimbabwean Universities during the COVID 19 era.' The findings proved that the majority of universities lack suitable ICT infrastructure, leadership support and training opportunities are minimal.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…The ICT regulations regarding online education are unclear (Rudhumbu et al, 2021). Apart from that, it was shown that most university lecturers adopted the lecturer-centred teaching styles, which has an impact on students' active participation in online learning.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
See 1 more Smart Citation
“…Globally universities implemented numerous digital innovations to migrate from face-to-face to online teaching [11]. Technologies that were commonly utilized were these among others: Moodle, Blackboard, Zoom, Google Classroom, Google Meet, Skype, Google Forms, Calendars, G-drive, Google Hangouts, Google Jam Boards, Drawings, YouTube Live, WhatsApp, Instagram, Twitter, Facebook Live and WebEx [12,13].…”
Section: Educational Innovationsmentioning
confidence: 99%
“…In Zimbabwe most of challenges that universities faced to conduct e-learning were poor ICT infrastructure, incapacitated users, lack of top management support to implement digital technologies, unstable and unreliable data bandwidth [11]. Similarly, In south Africa, university rural students were faced with erratic internet connectivity, short supply of electronic devices, Lack of internet accessibility infrastructure, user computer skills and expensive data bundles [8].…”
Section: E-learning Challenges Faced By South African and Zimbabwean ...mentioning
confidence: 99%